Cystathionine beta‐lyase is crucial for embryo patterning and the maintenance of root stem cell niche in Arabidopsis. (17th May 2019) - Liu, Guolan; Yang, Weiyuan; Zhang, Xiaojing; Peng, Tao; Zou, Yi; Zhang, Tao; Wang, Hao; Liu, Xuncheng; Tao, Li‐Zhen
Summary: The growth and development of roots in plants depends on the specification and maintenance of the root apical meristem. Here, we report the identification of CBL, a gene required for embryo and root development in Arabidopsis, and encodes cystathionine beta‐lyase (CBL), which catalyzes the penultimate step in methionine (Met) biosynthesis, and which also led to the discovery of a previous unknown, but crucial, metabolic contribution by the Met biosynthesis pathway. CBL is expressed in embryos and shows quiescent center (QC)‐enriched expression pattern in the root. cbl mutant has impaired embryo patterning, defective root stem cell niche, stunted root growth, and reduces accumulation of the root master regulators PLETHORA1 (PLT1) and PLT2. Furthermore, mutation in CBL severely decreases abundance of several PIN‐FORMED (PIN) proteins and impairs auxin‐responsive gene expression in the root tip. cbl seedlings also exhibit global reduction in histone H3 Lys‐4 trimethylation (H3K4me3) and DNA methylation. Importantly, mutation in CBL reduces the abundance of H3K4me3 modification in PLT1/2 genes and downregulates their expression. Overexpression of PLT2 partially rescues cbl root meristem defect, suggesting that CBL acts in part through PLT1/2 . Moreover, exogenous supplementation of Met also restores the impaired QC activity and the root growth defects of cbl . Taken together, our results highlight the unique role of CBL to maintain the root stem cell niche by cooperative actions between Met biosynthesis and epigenetic modification of key developmental regulators. Significance Statement: Growth and development depend on metabolic activities that properly support fundamental cellular functions, but mechanistic links are scarce. Here, we demonstrate that a quiescent center‐enriched CBL gene, encoding the second committed enzyme in methionine (Met) biosynthesis, plays a crucial role in root apical meristem maintenance by epigenetically influencing expression of the root master regulators PLETHORA (PTL1/2), elucidating a functional link between Met metabolic contribution and auxin‐dependent PLT‐ mediated maintenance of root stem cell niche.